Coverage analysis of coded orthogonal frequency division multiplexing (C-OFDM) based high speed railways (HSR) networks under different propagation scenarios - Chaudhuri Manoj Kumar Swain (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2024)
In this research work, investigation of percentage of coverage area is performed for coded OFDM (COFDM) based high-speed railways (HSR) communication networks. Different HSR scenarios such as viaduct, rural, suburban, urban and cutting etc. are considered for this analysis. Path loss models for these HSR scenarios are explored and analysed w.r.t the distance between base station (BS) and the receiver located at the train. Further, link budget of the network is investigated under these HSR scenarios. In addition, bit error rates (BER) of this communication networks are analysed under vehicular A and vehicular B channel models. For these investigation, sub-GHz frequency bands such as 2.5 GHz, 3.5 GHz, and 5.8 GHz are considered. It is observed that path loss in viaduct scenario is less as compared to other scenarios irrespective of frequency bands. It is also found that BER is more when the signal in propagated through vehicular B channel as compared to vehicular A channel. In addition, it is also noted that percentage of coverage area in viaduct scenario is more as compared to other HSR scenarios irrespective of frequency bands.